Testing methods for new pit latrine designs in rural and peri-urban areas of Malawi where conventional testing is difficult to employ. Issue 4 (23rd May 2016) - Chidya, R. C. G.; Holm, R. H.; Tembo, M.; Cole, B.; Workneh, P.; Kanyama, J.
Abstract : There is a trend towards participation of users in the design of appropriate sanitation facilities for low-income countries. Abstract : There is a trend towards participation of users in the design of appropriate sanitation facilities for low-income countries. However, testing the safety and durability of these technologies for rural and peri-urban communities is a challenge in low-income countries due to the lack of resources and access to conventional tests. This paper highlights testing methods used for pit latrine designs developed through participatory design approaches in Malawi. Two designs were tested with devised and/or conventional methods: (i) a corbelled pit latrine targeted for rural areas and (ii) an improved transitional pit latrine targeted for peri-urban areas. Devised testing methods proved to be useful and easy to implement by masons in the rural and peri-urban areas of Malawi. Novel pit latrine designs in Malawi require robust and innovative approaches to address the limited access to conventional tests. Both the conventional and devised testing methods demonstrated that the two designs have a satisfactory life-span and can support the users' load. The findings of this paper can be a model for the scale-up of integration of community ideas for participatory pit latrine design testing based in low-income countries where conventional testing is difficult to employ.